Paleomagnetic study of the late Neoproterozoic Bull Arm and Crown Hill formations (Musgravetown Group) of eastern Newfoundland: implications for Avalonia and West Gondwana paleogeography - Pisarevsky, Sergei; McCausland, P.; Hodych, J.; O'Brien, S.; Tait, J.; Murphy, J. (National Research Council Canada, 2012)
A paleomagnetic study of subaerial volcanic rocks and associated siltstones of the Ediacaran Bull Arm Formation in the Avalon Zone of Newfoundland revealed a stable bipolar, hematite-borne primary remanence supported by positive conglomerate, contact, and fold tests. Mean remanence directions in two distal areas (Bonavista and Argentia) are similar, indicating a low paleolatitude position of Avalonia at ~570 Ma. Redbeds of the overlying ~550 Ma Crown Hill Formation also carry a primary bipolar hematite-borne remanence with moderate inclination, indicating that Avalonia remained at low to medium paleolatitudes through the end of the Ediacaran. Combining our results with previously published paleomagnetic data of Avalonia suggests moderate-scale drift of Avalonia through low southern paleolatitudes through the latter half of the Ediacaran, providing a paleogeographic context for the development of the first complex metazoan life.